The colonisation of fynbos and disturbed sites by indigenous forest communities in the Southern Cape - Van Daalen, Johan Cornelis (Department of Biological Sciences, 2023)
The area covered by indigenous forests in the Southern Cape has been and is still diminishing as a result of 1 road construction (for example, 28 ha of indigenous' forest has recently been clear-felled for a new highway), power lines, settlements, fires (man-made and natural, for example the fires of 1869 and 1964) and agricultural activities. Furthermore, large areas are infested with exotic species such as Acacia melanoxylon ·(blackwood), A. mearnsii (black wattle) and different Eugalyptus and Pinus species. Although these species are useful timber and firewood species, they tend to establish themselves on disturbed patches in the indigenous forest and suppress the surrounding forest • trees. The present policy of the Directorate of Forestry and Environmental Conservation of the Department of Water Affairs, Forestry and Environmental Conservation (hereafter called Forestry) regarding these forests aim at their conservation and the reconstruction of small, damaged forest patches. Reconstruction is one of the five management classes for indigenous forests. The others are production, research, protection, and recreation. Especially during the last decade smaller areas were reconstructed, mainly by planting Podocarpus falcatus (kalander) and Ocotea bullata (stinkwood). Recently, other additional indigenous species are being used. A few experimental reconstruction plots have been laid out, the first one (in 1927) being the Taungya plots at